2019
DOI: 10.1002/jor.24472
|View full text |Cite
|
Sign up to set email alerts
|

Association of Superoxide‐Induced Oxidative Stress With Rotator Cuff Tears in Human Patients

Abstract: Rotator cuff degeneration is one of the factors contributing to rotator cuff tears. Oxidative stress is involved in tendon degeneration, and superoxide‐induced oxidative stress plays a pathological role in regulating the balance between oxidation and reduction. The role of oxidative stress in rotator cuff tears, however, is unclear. This study, therefore, aimed to investigate the contribution of superoxide‐induced oxidative stress to rotator cuff tears. Seventy patients were recruited and divided into two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 51 publications
(111 reference statements)
0
25
1
Order By: Relevance
“…ROS are short-lived molecules, which makes them difficult to be directly measured in vivo. Thus, we and other researchers have used dihydroethidium (DHE) staining to visualize ROS levels in freshly frozen tissue sections 35 , 40 . Figure 7 a shows that the DHE fluorescence intensities were significantly elevated in mouse heart tissues collected on day 3, 4 and 7 after TBI, and returned to similar level as sham-irradiated on day-14.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS are short-lived molecules, which makes them difficult to be directly measured in vivo. Thus, we and other researchers have used dihydroethidium (DHE) staining to visualize ROS levels in freshly frozen tissue sections 35 , 40 . Figure 7 a shows that the DHE fluorescence intensities were significantly elevated in mouse heart tissues collected on day 3, 4 and 7 after TBI, and returned to similar level as sham-irradiated on day-14.…”
Section: Resultsmentioning
confidence: 99%
“…ROS are short-lived molecules, which makes them difficult to be directly measured in vivo. In this study, we used DHE staining to visualize ROS levels in freshly frozen heart tissue sections based on our and others’ reports 35 , 40 . We acknowledge this limitation when interpreting our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol of the experiment was based on a previous study. 52 The DHE (Life Technologies Corporation) was adjusted to 10 mmol/L and applied to cover the entire section on the slide. After the sections on the slides were incubated in a chamber at 37°C for 30 minutes, they were washed twice using phosphate-buffered saline and enclosed with a cover glass.…”
Section: Dhe Fluorescence Intensity For Evaluation Of Oxidative Stressmentioning
confidence: 99%
“…11,19 Superoxide dismutase (SOD) is a major antioxidant enzyme that reduces the levels of reactive oxygen species in vivo. 33,34 Morikawa et al 36,37 demonstrated that rotator cuff degeneration was associated with excess oxidative stress in SOD1-deficient mice (SOD1 is 1 of 3 SOD isoforms that have different active centers and localities), and Yoshida et al 52 reported that imbalance of oxidative stress was implicated in the degeneration of rotator cuffs in patients with rotator cuff tears. However, it is unclear whether oxidative stress contributes to recurrent tear after ARCR.…”
mentioning
confidence: 99%
“…In vitro models are used to examine how dexamethasone can protect the tendon from degeneration, the roles of substrate stiffness and pulsed electromagnetic fields in tendon responses to inflammation, and tendon responses to mechanical loading . Finally, a series of papers examines the risk factors and susceptibility for rotator cuff disease and injury and the use of imaging modalities to assess changes to the cuff after repair . This special issue demonstrates exciting progress in the field towards understanding tendon pathogenesis and healing and presents a number of novel strategies to prevent disease progression and improve healing.…”
mentioning
confidence: 99%